Family and health evolving needs, responsibilities, and experiences - McCormick, Jennifer Higgins; Blair, Sampson Lee (Contemporary perspectives in family research, 2014)
Around the globe, families are often faced with a variety of health issues, often as a result of social, political, religious, and economic forces. Health issues affect both individual family members and the family unit as a whole, as well as impacting family relationships and structures. Illnesses, injuries, and health problems can strike at any time, and can have long-lasting consequences for individuals and their families. This multidisciplinary volume addresses the impact health issues have on individual family members and how this affects their family relationships. The chapters cover a wide range of health related topics including illness in adults and children, long term illness, mental health, and international perspectives. Through the use of a wide variety of methodological and theoretical perspectives, the family scholars in this volume provide considerable insight into the ways in which families and their members are affected by health, as well as how they adapt to and cope with health-related dilemmas.